A quarter-century report on neuromyelitis optica spectrum disorder in Thailand: A single-center tertiary care cohort - Tisavipat N. (2023)
Background: Neuromyelitis optica spectrum disorder (NMOSD) is an autoimmune demyelinating astrocytopathy with a high relapse-related disability. This is the largest long-term study of Thai NMOSD patients. Objectives: To compare characteristics and outcomes of aquaporin 4 (AQP4)-IgG-positive and AQP4-IgG-negative patients. Methods: A retrospective review of NMOSD patients at a university hospital was performed from January 1994 to July 2021. Results: From 165 NMSOD patients, the overall female-to-male ratio was 14:1. The mean onset age was 37.5 ± 14.3 years, and the median disease duration was 10.2 years. Transverse myelitis (46.1%) and optic neuritis (39.4%) were the most common presentations. Around 60% remained fully ambulatory at the last follow-up. Severe visual loss and ambulation aids were comparable in both groups, but the AQP4-IgG-positive had severe bowel and/or bladder dysfunction more often than the AQP4-IgG-negative (p = 0.026). The mortality rate was 6.7%, mainly from infection. Multivariate analysis showed that longer time-to-diagnosis and higher disability scores were associated with death. Diagnosis within one year yielded better visual and motor outcomes and lower annualized relapse rate. Conclusions: Thai AQP4-IgG-positive and AQP4-IgG-negative NMOSD patients had similar baseline characteristics. Relapse and mortality rates were comparable to global NMOSD patients. Diagnosis within one year promises better outcomes.